2015
DOI: 10.1007/s13197-015-1973-2
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and textural properties of pork patties as affected by buckwheat and fermented buckwheat

Abstract: This study was investigated to assess the effects of buckwheat (BW) and fermented buckwheat (FBW) on the proximate compositions, pH change, cooking quality, lipid oxidation, textural properties, and sensory characteristics of pork patties. Pork patties treated with BW and FBW were divided into six groups; Con, non-treated patties; T0, reduced fat patties; T1 and T2, addition of 1 and 3 % BW; FT1 and FT2, addition of 1 and 3 % FBW. FBW showed significantly higher antioxidant activity and total phenolic contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The results obtained are compatible with the findings of Olszak and others (), who demonstrated that the presence of active substances contained in buckwheat grains significantly influenced lower TBARS values after cold storage of baked pâté. Also Park and others () proved the inhibiting properties of buckwheat and fermented buckwheat on the creation of TBARS in pork patties during 14 d of storage at the temperature of 4 °C. The lowest level of lipid oxidation was found for the sample enriched with fermented buckwheat at 3%.…”
Section: Resultsmentioning
confidence: 96%
“…The results obtained are compatible with the findings of Olszak and others (), who demonstrated that the presence of active substances contained in buckwheat grains significantly influenced lower TBARS values after cold storage of baked pâté. Also Park and others () proved the inhibiting properties of buckwheat and fermented buckwheat on the creation of TBARS in pork patties during 14 d of storage at the temperature of 4 °C. The lowest level of lipid oxidation was found for the sample enriched with fermented buckwheat at 3%.…”
Section: Resultsmentioning
confidence: 96%
“…Belonging to the Polygonaceae family, buckwheat grains are rich in high flavonoids, dietary fiber, essential minerals, vitamins (e.g., B1, C, and E), and quality protein contents [ 49 ]. Apart from its gluten-free status, the proteins of buckwheat are rich in essential arginine and lysine amino acids and present excellent nutritional quality with high digestibility and bioavailability of amino acids.…”
Section: Nutritional Value Of Underutilized Grains As the Basis For T...mentioning
confidence: 99%
“…Therefore, it is necessary to advance the new ingredients and formulations, *  Corresponding author email: asmtbb@gmail.com especially to produce gluten-free meat products. Buckwheat (Fagopyrum esculentum Moench), a type of pseudo-cereal, has been suggested as a good alternative for celiac patients because it contains bio-quality proteins, high levels of dietary fiber, flavonoids and essential minerals (Park et al 2016). The chickpea (Cicer aeritinum L.) is the most consumed legume in the world.…”
Section: Intrоduсtiоnmentioning
confidence: 99%